2023
DOI: 10.3390/plants12122300
|View full text |Cite
|
Sign up to set email alerts
|

Deficit Irrigation Applied to Lemon Trees Grafted on Two Rootstocks and Irrigated with Desalinated Seawater

Abstract: The use of desalinated seawater (DSW) for irrigation in semi-arid regions is taking hold. Citrus tolerance to ions that predominate in DSW and water stress depends on the rootstock. Deficit irrigation was applied to DSW-irrigated lemon trees and grafted on rootstocks with different tolerance (Citrus macrophylla (CM) and sour orange (SO)). Plants were irrigated with DSW or Control treatment (distilled water), and, 140 days later, irrigation treatments were started: full irrigation (FI) or DI (50% of the volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…These concentrations were found to be within the range reported in previous studies [ 3 , 22 , 32 ]. In fact, recent studies [ 20 , 21 , 22 ] have detected toxic B levels in the leaf and a decline in physiological parameters in lemon trees with similar DSW water quality properties. In this sense, the second RO stage performed on the farm was able to decrease the overall DSW concentration of B below the phytotoxic threshold ( Figure 1 ), thereby avoiding possible detrimental effects on the tree.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These concentrations were found to be within the range reported in previous studies [ 3 , 22 , 32 ]. In fact, recent studies [ 20 , 21 , 22 ] have detected toxic B levels in the leaf and a decline in physiological parameters in lemon trees with similar DSW water quality properties. In this sense, the second RO stage performed on the farm was able to decrease the overall DSW concentration of B below the phytotoxic threshold ( Figure 1 ), thereby avoiding possible detrimental effects on the tree.…”
Section: Resultsmentioning
confidence: 99%
“…Those soils irrigated with DSW had the highest B concentration due to its higher concentration in the water source. Recent studies using DSW for citrus irrigation also found important accumulations of B in soils irrigated with DSW [ 21 ], albeit without the B content exceeding medium–high levels for agricultural soils (0.21–1.10 mg kg −1 soil) [ 34 ]. Consequently, the lower the proportion of DSW in the irrigation blend, the lower the concentration of B in the soil (DSW > MW > FW > DSW–B; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations